Respuesta :

Answer:

[tex](x-6)^2+(y-2)^2=16[/tex].

Step-by-step explanation:

[tex](x-h)^2+(y-k)^2=r^2[/tex] is the equation for a circle with center (h,k) and radius r.

You are given center (6,2) and radius 4.

So we will replace h with 6 and k with 2 and r with 4.

This gives us:

[tex](x-6)^2+(y-2)^2=4^2[/tex]

Simplify:

[tex](x-6)^2+(y-2)^2=16[/tex].

For this case we have that by definition, the equation of a circle is given by:

[tex](x-h) ^ 2 + (y-k) ^ 2 = r ^ 2[/tex]

Where:

[tex](h, k):[/tex]It is the center of the circle

r: It is the radius of the circle

According to the data we have to:

[tex](h, k) :( 6.2)\\r = 4[/tex]

Substituting:

[tex](x-6) ^ 2 + (y-2) ^ 2 = 4 ^ 2\\(x-6) ^ 2 + (y-2) ^ 2 = 16[/tex]

ANswer:

[tex](x-6) ^ 2 + (y-2) ^ 2 = 16[/tex]